On the Improvement of the Legislation Regulating the Powers of Public Authorities in the Field of Procurement of Goods, Works and Services for State and Municipal Needs - Solomonov, Evgeny V.; Yuritsin, Alexander A. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
On the basis of a systematic analysis of the powers of public authorities, as well as legislation on contract system in the field of procurement of goods, works and services for state and municipal needs, the Authors come to a conclusion about the need to improve the existing legislation in this field of public relations.